2017
DOI: 10.1038/eye.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness and safety between conbercept and ranibizumab for treatment of neovascular age-related macular degeneration. A retrospective case-controlled non-inferiority multiple center study

Abstract: Purpose To compare the efficacy and safety of conbercept and ranibizumab when administered according to a treat-and-extend (TREX) protocol for the treatment of neovascular AMD in China Patients and methods Between May 2014 and May 2015, 180 patients were treated in a 1:1 ratio using conbercept or ranibizumab from 4 hospitals. Patients received either conbercept 0.5mg or ranibizumab 0.5mg intravitreal injections. Follow-up time was one year and treated based on a TREX approach. Main outcomes and measures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…43 Conbercept is a natural conjugator of multiple targets of VEGFR, and so it is reasonable to speculate that it might exhibit a longer duration of action. 18 The concentrations of conbercept in the rabbit retina and choroid remained higher than the in vitro 50% inhibitory concentration value (7 ng/g) 44 over 34 days, indicating that a single 0.5 mg intravitreal injection may have an inhibitory effect against VEGF over the course of 81 days. 41…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…43 Conbercept is a natural conjugator of multiple targets of VEGFR, and so it is reasonable to speculate that it might exhibit a longer duration of action. 18 The concentrations of conbercept in the rabbit retina and choroid remained higher than the in vitro 50% inhibitory concentration value (7 ng/g) 44 over 34 days, indicating that a single 0.5 mg intravitreal injection may have an inhibitory effect against VEGF over the course of 81 days. 41…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, Huang et al 19 reported no significant difference in the visual improvement of patients with polypoidal choroidal vasculopathy between the conbercept and ranibizumab groups at 6 months; however, conbercept was superior to ranibizumab mono-therapy in the regression of polyps. Moreover, Cui et al 18 confirmed that conbercept and ranibizumab showed equivalent effects with respect to visual gain and reduction of central retinal thickness at 1 year, when administered according to a treat-and-extend protocol.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We read with interest the article by Cui et al [1]. In the article, the efficacy and safety of conbercept and ranibizumab for neovascular age-related macular degeneration were compared in a retrospective case-controlled non-inferiority study.…”
mentioning
confidence: 99%
“…We read with interest the recent article by Avci et al [1] reviewing the 51 cases of optic disc pit maculopathy (OPD-M) treated with pars plana vitrectomy. We would like to share our experience of OPD-M in a child with follow-up for 3 years and emphasize few learning points.…”
mentioning
confidence: 99%